A cultura espetacular das telenovelas: recepção, sexualidades e subjetividades em Paraíso Tropical-2007 - Borges, Dulcina Tereza Bonati (2011)
This work aims at investigating, besides the problematic of television in Brazil and interactivity among Medias, the processes and practices of reception of a soap opera from the following mediations: everyday life and subjectivity, what allows us to question the representations of sexuality, and the use of subjectivity on its interfaces with gender construction. Such concepts have taken place on television, making possible the analysis of the role played by the consuming of those representations, mainly in the big urban centers. Our proposal is to question the attraction Media exerts on contemporary man/woman, as well as their relationship with everyday television drama. The cultural industry and gender issues are pointed out having the Cultural History as theoretical support. This way we have studied the works of Chartier, Foucault, Edgar Morin, Stuart Hall, Canclini, Martin-Barbero, Maria Immacolata Vassallo de Lopes, Silvia Helena Simões Borelli, Vera da Rocha Resende, Scott, Rolnik, Tereza de Lauretis and Butler. The concepts approached were representations, new cultural studies, production, reception, mediations, and gender.